Pintar, se (re)apropriar e se relacionar: os conjuntos estilísticos no alto curso do rio Pardo Pequeno, Diamantina (MG). - Erik Alves de Oliveira (2016)
The region of Diamantina (MG) has been the subject of multiple efforts in archaeological research, especially those related to its pre-colonial past. This research is part of a context where several archaeological surveys and inquiries for the various pre-colonial occupations groups are present. The work will approach to the rock art of 24 archaeological sites in the upper course of the river Pardo Pequeno,tributary of the São Francisco river. The analysis had as theoretical and methodological north concepts as landscape and style, perceived as peculiar to each socio-cultural formation. These concepts were appropriate in the function research due to the need to understand the particular forms that suggest different themes, insertions of the sites in the landscape as well as possible relations established between them and the figurations. In the characterization of the figures were prioritized analyzes that incorporatedvarious stylistic and chronological criteria articulated with the attributes that compose the landscape. The survey results indicate the presence of different rock sets with different intentions, choices, relations with the landscape and with previous figures.